The USSR's economic strategy up to the year 2000: Aims, methods and chances of success - Dieter Lösch (Intereconomics, 1986)
The XXVIIth Congress of the CPSU marked the beginning of a new phase in Soviet economic policy which is to last to the year 2000. The Congress laid down the objectives for this phase and the means by which the objectives are to be achieved. Our article examines the question whether, or to what extent, the Soviet Union will be able to reach the goals it has set itself for this period.
Keywords: 330